Kajian Makanan Halal dan Industri Fashion dalam Tinjauan Konsumsi Islam - Pranata, Ahmad Adi; Masyhuri, Masyhuri; Julaihah, Umi; Asnawi, Nur; Meldona, Meldona (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
The demand for halal products is rising in the globalization era, covering food, beverages, and fashion, driven by the growth of the global Muslim population and awareness of consumption aligned with Islamic principles. This study aims to understand Muslim consumers’ perceptions and preferences towards halal products, explore producers' challenges in maintaining halal standards, and evaluate the role of halal certification in building consumer trust. A qualitative approach with a case study method was applied. Data were gathered through in-depth interviews with key informants, including PCNU administrators in Malang City, Muslim consumers, and halal food producers, alongside participatory observation and document analysis. Thematic and interactive analysis methods were employed. Findings reveal that cleanliness, taste quality, and adherence to halal standards are primary consumer considerations, while producers face challenges in maintaining halal compliance throughout the supply chain. Halal certification enhances product competitiveness and consumer trust. This study recommends SME education and mentoring to support halal industry growth.